Solitons in tunnel-coupled repulsive and attractive condensates - Shchesnovich, Valery S. [UNESP]; Cavalcanti, Solange B.; Kraenkel, Roberte A. [UNESP] (American Physical Society (APS), 2004)
The solitons in the condensate trapped in a double-well potential with far-separated wells were discussed. The s-wave scattering length had different signs in the two parts of the condensate. It was found by employing the coupled-mode approximation, that there were unusual stable bright solitons in the condensate, with the larger share of atoms being gathered in the repulsive part. The stability of such unusual solitons was derived from the quantum tunneling. The results show that the ground state of the system corresponded to weak coupling between the condensate parts.